Digital Financial Literacy and Financial Behavior: Pathways to Inclusion and Resilience - Rita Sarlawa (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The rapid growth of digital financial services has made the ability to understand and use online money tools essential for everyday financial decisions. This systematic literature review explores how digital financial literacy affects behaviors related to saving, spending, investing, and borrowing. This systematic literature review addresses these shortcomings by consolidating findings from 35 empirical studies published between 2010 and 2025. Following PRISMA 2020, the review identifies, evaluates, and thematically synthesizes quantitative, qualitative, and mixed-method research obtained through a rigorous search in a major academic database. Results show that higher digital financial literacy consistently promotes regular saving, disciplined budgeting, confident and diversified investing, and more responsible credit use. The positive effects are strongest for saving and investment, while spending and borrowing outcomes are more context-dependent, influenced by self-control, psychological biases, gender, income, and regulatory support. Seamless digital transactions can encourage impulsive spending or over-indebtedness when literacy is insufficient or safeguards are absent. These findings underscore the need for standardized digital financial literacy education within national inclusion strategies, gender-sensitive training programs, and fintech designs that incorporate behavioral nudges and fraud prevention features.